A prospective, randomized evaluation of the feasibility of exergaming on patients undergoing hematopoietic stem cell transplantation. (May 2018) - Schumacher, Helge; Stüwe, Sabrina; Kropp, Peter; Diedrich, Doreen; Freitag, Sebastian; Greger, Nico; Junghanss, Christian; Freund, Mathias; Hilgendorf, Inken
Abstract The positive effects of physical and sports therapy for strain dependent physical practice and improved quality of life (QoL) are well known. Nevertheless, the available capacities and problem-oriented therapies in the setting of hematopoietic stem cell transplantation (HSCT) are limited. We conducted a prospective, randomized study among 42 HSCT recipients in order to investigate the influence of exergaming on Nintendo Wii® or classical physiotherapy (PT) on physical fitness and psychological well-being. The trial included evaluation of muscle strength, endurance, physical activity, distress, QoL, anxiety, and depression. Within the first 2 weeks after HSCT endurance, muscle strength and physical well-being decreased, while the value of distress increased significantly in both groups. However, exergaming on Nintendo Wii® resulted in a decrease of anxiety and depression and improved emotional well-being, while the PT group showed a contrariwise pattern of these features. Analysis of the FACT-BMT revealed a decline of QoL domains 2 and 4 weeks after HSCT and an improvement afterwards. The decrease of functional status after HSCT was accompanied by a drop of QoL and an increase of distress in both groups. However, our prospective study demonstrates that exergaming using the Nintendo Wii® is feasible and well tolerated in HSCT recipients.